2011
DOI: 10.1038/nature10369
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of nucleotide-free dynamin

Abstract: Dynamin is a mechanochemical GTPase that oligomerizes around the neck of clathrin-coated pits and catalyses vesicle scission in a GTP-hydrolysis-dependent manner. The molecular details of oligomerization and the mechanism of the mechanochemical coupling are currently unknown. Here we present the crystal structure of human dynamin 1 in the nucleotide-free state with a four-domain architecture comprising the GTPase domain, the bundle signalling element, the stalk and the pleckstrin homology domain. Dynamin 1 oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

23
431
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 279 publications
(457 citation statements)
references
References 55 publications
23
431
0
3
Order By: Relevance
“…The PH domains of the outer molecules bind to a conserved surface of the stalk (Fig. 3a, b), to a similar site as in dimeric dynamin 1 2 (Extended Data Fig. 4b).…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…The PH domains of the outer molecules bind to a conserved surface of the stalk (Fig. 3a, b), to a similar site as in dimeric dynamin 1 2 (Extended Data Fig. 4b).…”
mentioning
confidence: 92%
“…3b), but not at the outer, non-assembled sides of the tetramer. Previous studies have shown that mutation of R399 in loop L2 S completely destroys higher-order assembly and dynamin function 2,3,11 . In our structure, R399 of an outer molecule forms salt bridges to E410 in α2 S and to E345 in L1N S in the outer and inner molecules of the opposite dimer, respectively.…”
mentioning
confidence: 96%
See 3 more Smart Citations